Estudio de biodisponibilidad de una mezcla de hidrocarburos en suelo modelo - Gómez Flores, Ana Paulina (Universidad Autónoma Metropolitana, 2016)
The soil is a complex porous matrix where contaminants due to human activity can be found. Hydrocarbons are highly persistant contaminants in soils and their persistancy in this environment is due to interactions between these contaminants and soil components. Bioremediation techno- logies use living organisms capacities to eliminate contaminants and are a promising alternative for hydrocarbons degradation, its success depends on the metabolic capacities of organisms and the weakness of the interactions between soil and contaminants. There are not known studies that clearly define the difference between the total amount of hydrocarbons in a contaminated soil, the fraction that can be quantified by experimental methods ( available ) and the fraction that has low interaction with soil that can actually be degradated by an organism ( bioavailable ). Acknowledging and differentiating this fractions becomes important when working with low concentrations of con- taminants, since it implies avoiding overestimations about remediation technologies results. The main objective in this work was the evaluation of a hydrocarbon mixture bioavailability in model soil by using a biosurfactant protein produced by a biocatalyst. The target molecules were hexadecane, phenanthrene and pyrene mixed at different proportions, and the soil, where experi- ments were performed, was defined as a model soil composed by a mixture of perlite and sand. The soil was spiked with an initial concentration of hydrocarbons of 800 mg(kg) − 1 , considered as 100 %. Availability was determined by two physicochemical methods: Soxhlet and microwave assisted ex- traction. From these analyses, only 20 % of the total hydrocarbon concentration was determined as available. With the aim to find out about the possible causes for low availability, porosity (0.58) and organic matter in soil were quantified (1.3 %). Soil organic matter was also identified as organic acids (hexadecanoic and octadecanoic acids). From the last results an experimental model of hy- drocarbon sequestration in organic matter contained in the soil pores was proposed. Bioavailability was determined by the quantification of desorbed hydrocarbons after these were put in contact with a biosurfactant protein produced by the biocatalyst (fungus Aspergillus brasiliensis treated with an electric field) in liquid culture. Bioavailability was determined as 2 % of initial hydrocarbon concentration, or 10 % from available hydrocarbons, which lead to the search for conditions that allow higher bioavailability. The availability and bioavailability results, as well as the sequestra-tion model, allowed us to develop a mathematical model that describes transport and reaction of the species: protein, protein-hydrocarbon complex and oxygen. The modelling of the system was carried out using the volume averaging method and it was divided into three scales: microscopic, intermediate and experimental; mathematical model development was divided into two stages: (i) averaging from the microscopic scale to the intermediate scale , (ii) averaging from the intermediate scale to the experimental scale. Subsequently, the mathematical model was solved in the experimental scale and a parametric analy- sis was performed. The parameters analized were Thiele modulus (relationship between reaction and diffussion in the soil), Biot number (transport towards and inside the soil), changes in the diffusivity coefficient, and efectiveness factor, which allowed the definition of conditions that fa- vour contaminant’s bioavailability in the system. Regarding the Thiele modulus for the protein and protein-hydrocarbon species, it was found necesary a high value for this dimensionless number, such result implies a higher rate for reaction than for diffusion for these species since the reaction for protein supposes the production of the protein-hydrocarbon complex, this last species guarantees bioavailability in the system. On the other hand, it is necessary to have a value close to one for the oxygen’s Thiele modulus, which means a similar reaction and diffusion rates in the model soil, this last assumption is made by the premise that the biocatalyst needs the constant presence of oxygen to degrade any of the other two species. Biot number was evaluated solely for oxygen, since it is the only species present in both gas and porous medium. The results indicate the need for a high value for the Biot number, which implies that the transport rate of oxygen towards the model soil is higher than the transport rate of oxygen inside the model soil, if such thing happens, oxygen’s permanence into the model soil will remain high, a necessary condition to mantain the biocatalyst active. With respect to effectiveness factor, it was corroborated that the biocatalyst’s effectivenes is higher only in a superficial layer of the soil since this is the zone where oxygen presence is pre- dominant for aerobic microorganisms activity, as the one present in the biocatalyst. The present work can be considered as one of the first attempts to relate in a deep way both theorical and experimental methodologies, besides, it sets ground for posterior analysis of organic contami- nants’s bioavailability in model matrixes, which may help in the comprehension of bioavailability studies in natural soils.; El suelo es una matriz porosa compleja en la que se pueden encontrar contaminantes producto de las actividades humanas. Los hidrocarburos son contaminantes altamente persistentes en suelos y su persistencia se debe a las interacciones que forman con los componentes del suelo. Las tecnologías de biorremediación utilizan las capacidades metabólicas de organismos vivos para eliminar contaminantes y son una alternativa prometedora para la degradación de hidrocarburos, su éxito depende de la naturaleza de las interacciones del suelo con los contaminantes. No se conocen trabajos que definan claramente la diferencia entre (i)la cantidad total de los hidrocarburos que se encuentran contaminando un suelo, (ii)la fracción cuantificable mediante métodos experimentales ( disponibles ) y (iii)la fracción que interacciona débilmente con el suelo y que realmente puede ser aprovechada por un organismo (biodisponibles ). Conocer y diferenciar estas fracciones cobra importancia cuando las magnitudes de las concentraciones de los contaminantes son bajas, ya que la diferencia implica evitar sobreestimaciones acerca de los resultados de cualquier tecnología de remediación. El objetivo de este trabajo fue evaluar la biodisponibilidad de una mezcla de hidrocarburos utilizando una proteína biosurfactante producida por un biocatalizador. Como moléculas de estudio se utilizaron los hidrocarburos hexadecano, fenantreno y pireno mezclados en diferentes proporciones y el suelo donde se realizaron los experimentos se definió como una mezcla modelo conformada por arena y agrolita. La concentración inicial de hidrocarburos añadida al suelo modelo fue de 800 mg (kg) − 1 y se consideró como la base porcentual de cálculo. La disponibilidad se determinó por dos métodos: Soxhlet y extracción asistida por microondas. Del total inicial de la mezcla de hidrocarburos, se cuantificó 20% de hidrocarburos disponibles. La baja disponibilidad fue asociada a la materia orgánica contenida en el suelo modelo (1.3 %), que se identificó como ácidos orgánicos (hexadecanóico y octadecanóico). A partir de los dos resultados anteriores se propuso un modelo experimental de secuestro de la mezcla de hidrocarburos en la materia orgánica contenida en los poros del suelo. La biodisponibilidad de la mezcla de hidrocarburos se determinó cuantificando la cantidad de hidrocarburos desorbidos con una proteína biosurfactante; esta proteína fue obtenida previamente de un reactor airlift durante la degradación de hidrocarburos en suspensión por el biocatalizador (hongo Aspergillus brasiliensis inmovilizado en agrolita previamente tratado con una corriente eléctrica). Se determinó una biodisponibilidad del 2 % de los hidrocarburos iniciales totales, o 10 % de los hidrocarburos disponibles, lo que condujo a la búsqueda de condiciones que permitieran incrementar la biodisponibilidad de los contaminantes. Los resultados de disponibilidad, biodisponibilidad y el modelo de secuestro propuesto permitieron desarrollar un modelo matemático que describe el transporte y reacción de las moléculas: proteína, complejo proteína- hidrocarburo y, oxígeno en el suelo modelo. El modelado del sistema se dividió en tres escalas: microscópica, intermedia y experimental; el desarrollo del modelo matemático se consiguió utilizando el método del promedio volumétrico y se dividió en dos etapas: (i) promediado de la escala microscópica a la intermedia, (ii) promediado de la escala intermedia a la experimental. Posteriormente, se resolvió el modelo en la escala experimental y se realizó un análisis paramétrico donde se evaluaron el módulo de Thiele (relación reacción y difusión en el suelo modelo), el número de Biot (transporte hacia y dentro del suelo modelo), cambio en el coeficiente de difusión para cada molécula y el factor de efectividad, lo que permitió definir condiciones bajo las cuales la biodisponibilidad de los contaminantes se incrementa. Con respecto al módulo de Thiele para la proteína y el complejo proteína-hidrocarburo, se encontró que es necesaria una tasa de reacción mayor a la tasa de difusión para estas moléculas, ya que la reacción de la proteína implica la producción del complejo proteína-hidrocarburo, esta última molécula es con la que se puede asegurar biodisponibilidad de los contaminantes en el sistema. Por otra parte, es necesario que el módulo de Thiele para oxígeno sea un valor cercano a uno, lo que significa que la tasa de reacción sea parecida a la tasa de difusión de esta molécula en el suelo modelo, lo anterior debido a que el biocatalizador necesita una constante presencia de oxígeno para que pueda consumir a cualquiera de las otras dos moléculas. El número de Biot fue evaluado únicamente para el oxígeno y los resultados indican que es necesario un valor de número de Biot alto, lo que implica que la cantidad de oxígeno que se transporta hacia el suelo modelo sea mayor a la cantidad que se transporta dentro del mismo, ya que si eso sucede la permanencia de oxígeno será alta en el suelo, así el biocatalizador tendrá una mayor oportunidad de aprovecharlo. Con lo que respecta al análisis del factor de efectividad se corroboró que la eficiencia del biocatalizador es mejor en la parte superficial del suelo modelo, ya que, en esta zona, la presencia de oxígeno es determinante para la actividad de microorganismos aerobios, como el que conforma al biocatalizador. Este trabajo es el primero en relacionar de manera profunda estudios de transporte de masa en medios porosos y resultados experimentales, además sienta las bases para posteriores análisis de biodisponibilidad de contaminantes orgánicos en matrices modelo, lo que puede ayudar en la comprensión de estudios de biodisponibilidad en suelos naturales.